PENGARUH KOMPETENSI, SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL TERHADAP KINERJA KEUANGAN KOPERASI SIMPAN PINJAM SE-KECAMATAN KEDIRI - Ni Putu Trisna Windika Pratiwi; Ni Wayan Kusuma Dewi; Ni Wayan Yuniasih (Jurnal Widya Akuntansi dan Keuangan, 2024)
The purpose of this research is to analyze the relationship between savings and loan cooperatives' financial performance and factors such as competency, accounting information systems, and internal control in the Kediri area. Participants included everyone on the books at the Cooperative and UKM Office in Tabanan Regency who had worked in the KSP Kediri District and used the accounting information system. Purposive sampling was used to select the study's sample size of 69 participants, and the results were analyzed with multiple linear regression methods. This study's findings suggest that competence has a beneficial and statistically significant impact on economic outcomes. The Financial Performance is significantly impacted for the better by the Accounting Information System. The quality of an organization's internal controls has a noticeable and beneficial impact on its bottom line. Based on the findings of this study, it is imperative that Savings and Loan Cooperatives in the Kediri District be able to provide their employees with on-the-job training in the future. Competent workers will be able to contribute most effectively to the success of the business.